Contrasting patterns of fig wasp communities along Mt. Wilhelm, Papua New Guinea. (30th March 2020) - Souto‐Vilarós, Daniel; Houadria, Mickal; Michalek, Jan; Sisol, Mentap; Isua, Brus; Kuyaiva, Thomas; Weiblen, George D.; Novotny, Vojtech; Segar, Simon T.
Abstract: The fig (Moraceae) and pollinating fig wasp (Agaonidae) mutualism is best known as a model system for the study of coevolution in plant–pollinator interactions and its central role in shaping vertebrate communities in tropical forests. Figs also host myriad antagonistic parasitic fig wasps which impose costs on both partners threatening mutualism stability. Spatiotemporal variation in parasitic wasp abundance is a key factor in mitigating these effects. Because fig wasps are temperature sensitive and likely vary in their ability to traverse environmental gradients, we expect community assemblages and abundance of both pollinating and non‐pollinating fig wasps to respond to changes along an elevational gradient. In the present study, we compare the fig wasp communities and abundance of three fig species growing along the slopes of the Mount Wilhelm altitudinal gradient in Papua New Guinea. We quantified wasps from over 100 male fig trees and calculated seed set for 55 female trees along each of the species' distribution on the transect. Our results show that the abundance of both pollinating and non‐pollinating fig wasps follow a mid‐elevation peak, consistent with fig species richness found in the same transect. The patterns, however, are different according to the host's species distribution. Seed set remained relatively constant along the gradient for all species with some decrease along higher elevations, potentially affecting connectivity along the gradient. As suggested for insects in general, temperature and habitat diversity appear to play a fundamental role in the species richness and abundance of fig wasps.